Pengaruh Hambatan Samping Terhadap Kinerja Lalu Lintas Jalan Nasional (Studi Kasus Jalan Proklamator Raya – Pasar Bandarjaya Plaza) - Syaputra, Randy; Sebayang, Syukur; Herianto, Dwi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
The high value of side friction on the road cause a decrease in performance of the road. Theamount of side friction affects the capasity and speed of ride vehicles. The aim of this research wasto analize the factors that affect the performance degredation of traffic condition on some sidefriction and determine planning solutions to improve the traffic performance.This research are obtained by doing survey of traffic volume (LHR) to see the density of vehicles,then surveys the side friction to see the influence of interference and spot speed surveys bothdistrubed and undistrubed side friction. This research doing in 500 meters in a market segment ofBandarjaya Plaza. Next calculation use the Manual Capasity of Indonesian Road in 1997 for theOutside Urban Road.Based on calculation, then obtained the highest value of the degree of saturation of 1,01 to lineBandarjaya with a volume of vehicles by 1395 pcu/hours, while the capacity of road only 1384pcu/hours. It is indicate the state of the roads is very saturated, so that the necessary repairs theroad performance. The highest level of side friction affecting road performance degredation in theform of vehicles in and out the side road area, so it made procurement solutions median crossingthe road in an attempt to eliminate the vehicle.Keywords : side friction, traffic volume, national road